Individual Counseling for Dyslexic Students - Rosita, Tita; Annisa, Yulia Nur (Academia Edu Cendekia Indonesia (AEDUCIA), 2022)
Students with dyslexia have difficulty reading so they are less able to understand learning material which has an impact on low academic, social and emotional scores. Based on these conditions, dyslexic students need counseling in dealing with these problems. The purpose of this study is to analyze the description of the condition of dyslexic students and individual counseling for dyslexic children. The research method is to use a literature review. The results of the study obtained data that dyslexia is caused by neurological factors that cause deficits in the areas of working memory and auditory temporal memory of dyslexia. This condition causes less accuracy in reading in dyslexic children. Individual counseling in schools carried out by Guidance and Counseling teachers can develop coping strategies to reduce the impact of stigma and difficulties on the learning process.